Analysis of magnetorefractive effect in La₀.₇Ca₀.₃MnO₃ thin films in the IR spectral range - Yurasov, A.N.; Bakhvalova, T.N.; Telegin, A.V.; Sukhorukov, Yu.P. (Functional Materials, 2012)
We have reported the results of investigation of a magneto refractive effect on magnetoreflection and magnetotransmission modes in La₀.₇Ca₀.₃MnO₃ manganite thin films and crystals in the middle IR spectral range. The effects can reach several percents for single crystals and up to 20—40 % for thin films near Curie temperature. It was shown that the magnitude and spectra of the magnetorefractive effect strongly depend on magnetoresistance and optical properties of manganites. The overall qualitative agreement was obtained between the calculated in the framework of the effective medium approach data and experimental data.